Proceedings of Advancing Astrophysics With the Square Kilometre Array — PoS(AASKA14) 2015
DOI: 10.22323/1.215.0067
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Physics and Evolution of Galaxies and Galaxy Clusters with SKA Continuum Surveys

Abstract: In this chapter we provide an overview of the science enabled by radio continuum surveys in the SKA era, focusing on galaxy/galaxy cluster physics and evolution studies, and other relevant continuum science in the > 2020 scientific framework. We outline a number of reference radio-continuum surveys for SKA1 that can address such topics, and comprehensively discuss the most critical science requirements that we have identified. We highlight what should be achieved by SKA1, to guarantee a major leap forwards wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…14 we show the faint end of our source counts with two different definitions for nonoverlapping populations (left and right panels) and extrapolations down to radio fluxes of ∼10 nJy, encompassing the detection limits of SKA1 Ultra Deep, Deep, and Wide surveys (Prandoni & Seymour 2015). In a zero-order attempt to extrapolate the counts, not intended to be related to any physical model, we use a simple linear fit to the four faintest data points (S 1.4 GHz < 80 µJy) for each of the various radio-detected subpopulations.…”
Section: Expectations For Future Surveys Based On Simple Extrapolationsmentioning
confidence: 99%
See 3 more Smart Citations
“…14 we show the faint end of our source counts with two different definitions for nonoverlapping populations (left and right panels) and extrapolations down to radio fluxes of ∼10 nJy, encompassing the detection limits of SKA1 Ultra Deep, Deep, and Wide surveys (Prandoni & Seymour 2015). In a zero-order attempt to extrapolate the counts, not intended to be related to any physical model, we use a simple linear fit to the four faintest data points (S 1.4 GHz < 80 µJy) for each of the various radio-detected subpopulations.…”
Section: Expectations For Future Surveys Based On Simple Extrapolationsmentioning
confidence: 99%
“…This makes the VLA-COSMOS 3 GHz Large Project to-date the deepest radio continuum survey over a relatively large field. Combined with the rich COSMOS multiwavelength data this survey, thus, yields a unique data set to test the composition (i.e., fractions of various galaxy types) of the faintest radio source populations that can currently be probed; it also allows us to use these findings to make predictions for the populations to be detected by future surveys, such as those planned with the Square Kilometre Array (SKA), and its precursors (Prandoni & Seymour 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These past surveys have shown that deep observations at high angular resolution ( 1 ) with exquisite panchromatic coverage are critical to comprehensively study the radio properties of the main galaxy populations, avoiding cosmic variance with large area coverage (e.g., Padovani et al 2009;Padovani 2011;Smolčić et al 2008Smolčić et al , 2009bSmolčić 2009;Smolčić & Riechers 2011;Seymour et al 2008;Bonzini et al 2012Bonzini et al , 2013. In this context, large area surveys down to unprecedented depths are planned with new and upgraded facilities (e.g., VLA, Westerbork, Australian Square Kilometre Array Pathfinder, MeerKAT, and Square Kilometre Array; e.g., Jarvis 2012; Norris et al 2011Norris et al , 2013Norris et al , 2015Prandoni & Seymour 2015). Figure 1 shows the 1σ sensitivity of each survey as a function of the area covered for past, current, and future radio continuum surveys.…”
Section: Introductionmentioning
confidence: 99%